2008
DOI: 10.1089/vbz.2008.0006
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Identification ofRickettsiaSpecies in the Northeast of Italy

Abstract: This study was carried out using Ixodes ricinus ticks collected during 2005 and 2006 from the Friuli Venezia Giulia (FVG) region in the northeastern part of Italy and an area along the Slovenian side of the western border of Italy. The results indicate that Rickettsia spp. is widely distributed throughout these areas, with the greatest prevalence in the central part of the FVG region. The prevalence of Rickettsia spp. was 4.5% during 2005 and 6.1% during 2006. By sequencing the 16S rRNA gene, we show for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 22 publications
1
23
2
1
Order By: Relevance
“…The detection of R. monacensis in I. ricinus ticks adds to findings in surrounding countries, where the presence of this species has been confirmed (30,32,49,54). However, finding this high proportion of R. raoultii (40.9% of Rickettsia species-positive ticks) and one R. slovaca-positive I. ricinus tick in our investigation was surprising, as these species are usually associated with Dermacentor ticks (55, 57).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The detection of R. monacensis in I. ricinus ticks adds to findings in surrounding countries, where the presence of this species has been confirmed (30,32,49,54). However, finding this high proportion of R. raoultii (40.9% of Rickettsia species-positive ticks) and one R. slovaca-positive I. ricinus tick in our investigation was surprising, as these species are usually associated with Dermacentor ticks (55, 57).…”
Section: Discussionsupporting
confidence: 55%
“…The prevalence of Rickettsia spp. in questing I. ricinus ticks in the countries surrounding Austria typically does not exceed 20% (30,32,(49)(50)(51)(52)(53)(54). A previous Austrian study found a higher rate of 35.6% in ticks from the 2005 collection (15).…”
Section: Discussionmentioning
confidence: 92%
“…strain Davousti, previously found in Amblyomma tholloni ticks in Africa, was detected in Ixodes species ticks collected from migratory birds in Sweden (323). Furthermore, a sequence with high homology to that of "Rickettsia limoniae" was detected in I. ricinus ticks from the Italian Alpine zone (324). Rickettsia sp.…”
Section: Nonvalidated Incompletely Described or Uncultivated Speciesmentioning
confidence: 70%
“…Furthermore, the incidence of TBE in these regions has increased from 0.06 to 0.88 cases per 100 000 inhabitants in the same time frame (Rizzoli et al, 2009). Importantly, TBEV has been isolated and identified in most of the regions where human cases have been reported (Hudson et al, 2001;Beltrame et al, 2006;Cruciatti et al, 2006;Floris et al, 2006;D'Agaro et al, 2009). However, previous studies undertaken primarily in the Veneto and Trentino regions have shown a lower prevalence of TBEV in Italian tick populations compared with other European sites where TBEV is endemic (Hudson et al, 2001), whilst phylogenetic analyses indicate that only strains of the European subtype very similar to the Austrian Neudoerfl strain have been found in Italian TBEV populations (Hudson et al, 2001;Floris et al, 2006;D'Agaro et al, 2009).…”
Section: Introductionmentioning
confidence: 99%